2018
DOI: 10.1039/c8ra01856a
|View full text |Cite
|
Sign up to set email alerts
|

Duckweed systems for eutrophic water purification through converting wastewater nutrients to high-starch biomass: comparative evaluation of three different genera (Spirodela polyrhiza, Lemna minor and Landoltia punctata) in monoculture or polyculture

Abstract: This study provides a new insight into the application of duckweed in eutrophic water advanced treatment and starch production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 53 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…Lemnaceae (commonly known as water lens or duckweed) is a family of monocotyledonous water plants (Landolt, 1986;Landolt and Kandeler, 1987;Sree et al, 2016) characterized by the fastest growth rates among flowering plants (Sree et al, 2015b;Ziegler et al, 2015). As a consequence, the rate of biomass production is high, which provides the basis for different practical applications of duckweeds in the areas of food and feed sustainability (Landolt and Kandeler, 1987;Appenroth et al, 2017Appenroth et al, , 2018Sonta et al, 2019) and biotechnology (Zhao et al, 2015;Chen et al, 2018;Kaur et al, 2018;Ren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lemnaceae (commonly known as water lens or duckweed) is a family of monocotyledonous water plants (Landolt, 1986;Landolt and Kandeler, 1987;Sree et al, 2016) characterized by the fastest growth rates among flowering plants (Sree et al, 2015b;Ziegler et al, 2015). As a consequence, the rate of biomass production is high, which provides the basis for different practical applications of duckweeds in the areas of food and feed sustainability (Landolt and Kandeler, 1987;Appenroth et al, 2017Appenroth et al, , 2018Sonta et al, 2019) and biotechnology (Zhao et al, 2015;Chen et al, 2018;Kaur et al, 2018;Ren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…TN and TP removal efficiencies were calculated using the following equation Removal efficiency true(%true)=C0CnormaltC0×100% where C 0 is the initial TN or TP concentration (mg L −1 ); C t is the TN or TP concentration (mg L −1 ) at time t .…”
Section: Methodsmentioning
confidence: 99%
“…Although Chen et al [19] found that L. punctata has a good repair effect on eutrophic water, little is known about the changes in the physiological and biochemical indexes of L. punctata during the repair process. In this study, we found that after 15 days of co-cultivation of L. punctata and the gradient density M. aeruginosa was higher than the "water bloom" burst level, the biomass of L. punctata showed a trend of increasing first and then decreasing.…”
Section: Effects Of M Aeruginosa On the Growth Of L Punctatamentioning
confidence: 99%